Effect of Terminal Drought Stress on Morpho-physiological Traits of Wheat Genotypes: Drought Stress Effect on Wheat - Baloch, Muhammad Jurial; Chandio, Irfan Ali; Arain, Muhammad Ahmed; Baloch, Amanullah; Jatoi, Wajid Ali (Biological Sciences - PJSIR, 2016)
Development of wheat varieties with low moisture requirements and their ability to withstand moisture stress may cope-up well with the on-coming peril of drought conditions. Ten wheat genotypes including two new strains, PBGST-3, Hero, Bhittai, Marvi, Inqlab, Sarsabz, Abadgar, Kiran, Khirman and PBGST-4 were sown in split plot design with factorial arrangement in four replications at Experimental Field, Department of Plant Breeding & Genetics, Sindh Agricutlure University, Pakistan during 2012-13. The results revealed that water stress caused significant reductions in all morpho-physiological traits. The genotypes differed significantly for all the yield and physiological traits. The interaction of treatments × genotypes were also significant for all the traits except plant height, productive tillers/plant, grains/spike and harvest index, were non-significant which indicated that cultivars responded variably over the stress treatments suggesting that breeders can select the promising genotypes for both stress and non-stress environments. Among the genotypes evaluated Bhittai, Kiran-95, PBGST-3 and Sarsabz showed good performance as minimum reductions occurred under terminal stress conditions for all the traits studied. Hence, above mentioned genotypes were considered as drought tolerant group. The high positive correlations of physiological traits like chlorophyll content and relative water content with almost all yield traits indicated that these physiological traits could serve as reliable criteria for breeding drought tolerance in wheat. The negative correlations of electrolyte leakage with several important yield traits indicated that though this physiological trait has adverse effect on yield attributes, yet it could reliably be used to distinguish between drought tolerant and susceptible wheat genotypes.